Angular Momentum, Statistical Equilibrium and Sequential Fission in Very Asymmetric Systems - Morrissey, D. J.; Wodjniak, G. J.; Sobotka, L. G.; Pacheco, A. J.; Hsu, C. C.; McDonald, R. J.; Moretto, L. G. (Springer-Verlag, 1982)
Fil: Morrissey, D. J. Institute, Michigan State University; Estados Unidos